Congenital Gingival Granular Cell Tumor: Case Report - Kemal Uzunlar, Ali (Annals of Medical Research, 2021)
Aim: In this study we present a rare case of congenital gingival granular cell tumour with intraoral location.
Keywords: Congenital granular cell tumour